Effect of Basalt Fibers on The Flexural Behavior of Beams Reinforced With BFRP Bars - AlHafiz, Abdul Rahman M.Musif (2018)
A Master of Science thesis in Civil Engineering by Abdul Rahman M.Musif AlHafiz entitled, “Effect of Basalt Fibers on The Flexural Behavior of Beams Reinforced With BFRP Bars”, submitted in May 2018. Thesis advisor is Dr. Farid Abed. Soft and hard copy available.